Case Report: Microfragmented Adipose Tissue Drug Delivery in Canine Mesothelioma: A Case Report on Safety, Feasibility, and Clinical Findings - Zeira, Offer; Ghezzi, Erica; Pettinari, Letizia; Re, Valentina; Lupi, Davide M.; Benali, Silvia L.; Borgonovo, Simone; Alessandri, Giulio; Petrella, Francesco; Paroni, Rita; Dei Cas, Michele; Tremolada, Carlo; et al. (Frontiers in Veterinary Science, 2021)
Mesothelioma is a rare lethal tumour of dogs and humans, involving cavities of the body. Dogs are considered a model for new drugs and therapeutic methods since they present spontaneous diseases similar to humans. Microfragmented adipose tissue (MFAT) and uploaded by Paclitaxel (PTX), is a drug delivery medium providing slow release of chemotherapic drug. A dog affected by pleural, pericardial and peritoneal mesothelioma, was treated by intracavitary ultrasound guided 17 injections of MFAT-PTX in 22 months. A long lasting improvement of general conditions was observed, treatment well tolerated and no toxicity or hypersensitivity reported. Pharmacokinetic (PK) data indicated low drug localization in the circulatory system and tendency to enter or remain in the extravascular compartments of the body. Indeed, low levels of free circulating drug for a short time produced low toxicity, whereas higher intracavitary PTX concentration can have major pharmacological efficacy. To our knowledge this is the first time that mesothelioma is treated using such a procedure and should be considered as a novel therapeutic approach. The low systemic absorption suggest possible role of MFAT-PTX for loco-regional/intratumoral therapy also useful in other type of tumours and further investigation is warranted.